Organizational Climate Management, Rewards, Emotional Intelligence, Job Satisfaction and Organizational Commitment in Insurance Agent in The Jabodetabek Region - Sutrasna, Yudi; Duha, Junindra (Graduate Program Magister Manajemen Pendidikan, 2022)
Insurance agents are the front-line people who win premiums for insurance companies. Therefore, its presence must be promoted and maintained in order to have a high degree of organizational ties with the company/organization. Agent development and maintenance efforts can be driven by a variety of variables that are directly or indirectly influenced, including organizational climate, achievement, emotional intelligence, and job satisfaction. This study uses descriptive and explanatory methods; the sample used is the 10 life insurance companies with the largest market share in Greater Jakarta (Jabodetabek). Data analysis using bin and path analysis. Regional interval analysis results show that organizational climate is favorable; rewards, emotional intelligence, job satisfaction, and organizational commitment are at high levels. Additionally, the results of the path analysis show 1) organizational climate and emotional intelligence, which, in turn, partially or simultaneously affect life insurance agents, 2) organizational climate and job satisfaction, which, in turn, partially or simultaneously affect life insurance agents, 3) organizational climate and rewards, organizational life commitment Partially or simultaneously from insurance agents, 4) organizational climate and rewards affect organizational engagement through life insurance agents' emotional intelligence, 5) organizational climate and rewards affect organizational engagement through life insurance agents' job satisfaction, 6) emotional intelligence and Job satisfaction partly or simultaneously affects the organizational engagement of life insurance agents.